Pelatihan Pengajar Pendamping pada Sekolah Minggu Buddha Vihara Siripada Tangerang Selatan - Liong Houw; Keti Keti; Bayu Jati Pamungkas (STAB Maitreyawira, 2020)
This research highlights the accompanying teacher training at the Buddha Sunday School (SMB) at Vihara Siripada in South Tangerang. The role of the accompanying teacher at Buddhist Sunday School Vihara Siripada has important functions in helping to develop the potential of each of the personal students of Buddha Sunday School. Therefore, the escort teacher at the Buddha Sunday School Vihara Siripada should have adequate skills and skill in conducting mentoring. One way to improve skills and skill is to follow public speaking training and the development of curriculum materials of the Sunday School of Buddhist Kemenag RI. The above skills are supported with a deepening of Dhamma material, and multi-media selection. Training in the form of seminars and Dhamma Talk adds the ability to speak, brave, and eagerly accompany the participants of the Buddha Sunday School Vihara Siripada. Skilled in developing learning materials about the Dhamma, choosing the right media, and skilled speaking good and right in front of the Buddhist Sunday School students.